Proceedings of the 19th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2013
DOI: 10.1145/2487575.2487602
|View full text |Cite
|
Sign up to set email alerts
|

Approximate graph mining with label costs

Abstract: Many real-world graphs have complex labels on the nodes and edges. Mining only exact patterns yields limited insights, since it may be hard to find exact matches. However, in many domains it is relatively easy to define a cost (or distance) between different labels. Using this information, it becomes possible to mine a much richer set of approximate subgraph patterns, which preserve the topology but allow bounded label mismatches. We present novel and scalable methods to efficiently solve the approximate isomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Chemical Compound Categorization is important in biomedical research for testing whether a compound is active to a specific cancer, such as melanoma. For melanoma cancer, determining activities of a molecule is expensive as it requires time, efforts, and expensive resources [19] to conduct biological assay. In reality, some similar bioassay tasks 1 , such as an anti-cancer test for prostate, may be available.…”
Section: A Multi-task Graph Classification: Motivationmentioning
confidence: 99%
“…Chemical Compound Categorization is important in biomedical research for testing whether a compound is active to a specific cancer, such as melanoma. For melanoma cancer, determining activities of a molecule is expensive as it requires time, efforts, and expensive resources [19] to conduct biological assay. In reality, some similar bioassay tasks 1 , such as an anti-cancer test for prostate, may be available.…”
Section: A Multi-task Graph Classification: Motivationmentioning
confidence: 99%
“…The work in [25] detects clones in UML models such as class diagrams, but structure similarity is not considered when comparing two fragments. For subgraph detection, there are various methods considering frequent subgraph mining [26,27] and subgraph isomorphism [28], but the objective of these methods is significant different from this paper. These methods aim to discover arbitrary connected subgraphs instead of fragments, so many of them are useless for reference sub-process extraction which makes them not suitable for our purpose.…”
Section: Related Workmentioning
confidence: 99%
“…The investigation of the proteins' spatial shape may provide important functional and structural insights (Clark et al, 1991;Cootes et al, 2003). Indeed, protein structures have been interpreted as graphs of amino acids and studied based on graph theory concepts (Borgwardt et al, 2005;Anchuri et al, 2013;Dhifli et al, 2014;Dhifli and Nguifo, 2015;Dhifli et al, 2017;Saha et al, 2017;Mrzic et al, 2018;Sugiyama et al, 2018). In this regard, some works were interested in the study of protein structures based on their graph properties and involved the use of topological classifications as in Bartoli et al (2007), where it has been shown that proteins can be considered as small-world networks of amino acids.…”
Section: Introductionmentioning
confidence: 99%